2021
DOI: 10.1002/ehf2.13198
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin‐induced and trastuzumab‐induced cardiotoxicity in mice is not prevented by metoprolol

Abstract: Aims Our objectives were to validate a murine model of chronic cardiotoxicity induced by Doxorubicin (Dox) and Trastuzumab (Trast) and to test the potential cardio-protective effect of metoprolol. Methods and results Male C57Bl6 mice were intraperitoneally injected during 2 weeks with Dox (24 mg/kg) or saline, and then with Trast (10 mg/kg) or saline for two more weeks. Half of the mice received metoprolol (100 mg/kg). Cardiotoxicity was defined by a decline in left ventricular ejection fraction (LVEF) ≥ 10 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Puma contributes to p53-mediated apoptosis by indirect induction of mitochondrial outer membrane permeabilization and direct binding with Bcl-2 proteins, preventing their inhibitory effects on Bax. Moreover, DOX binds to topoisomerase IIB (TOP2B) protein and DNA, resulting in double-strand DNA breaks, as well as activating the DNA damage pathway with induction of cardiomyocyte apoptosis [ 25 ]. Normally, the cardiomyocytes attempt to repair this damage via the Neuroglin-HER2 pathway but, in the presence of Trz, an anti-HER2 binding agent, the HER2 function would be compromised, resulting in significant damage to cardiomyocytes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Puma contributes to p53-mediated apoptosis by indirect induction of mitochondrial outer membrane permeabilization and direct binding with Bcl-2 proteins, preventing their inhibitory effects on Bax. Moreover, DOX binds to topoisomerase IIB (TOP2B) protein and DNA, resulting in double-strand DNA breaks, as well as activating the DNA damage pathway with induction of cardiomyocyte apoptosis [ 25 ]. Normally, the cardiomyocytes attempt to repair this damage via the Neuroglin-HER2 pathway but, in the presence of Trz, an anti-HER2 binding agent, the HER2 function would be compromised, resulting in significant damage to cardiomyocytes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that the usefulness of β-blockers against chemotherapy-related cardiotoxicity is controversial. For instance, an in vitro experimental study revealed the inability of metoprolol to prevent cardiotoxicity in C57Bl6 mice treated with Dox and trastuzumab ( 70 ). Similarly, Avila et al ( 66 ) demonstrated carvedilol's inability to mitigate ATC-induced chronic cardiotoxicity in breast cancer patients ( 67 ).…”
Section: Dic: Are Today's Cancer Survivors the Future Cvd Patientsmentioning
confidence: 99%
“…This drug results in cardiotoxicity, which is manifested as a progressive and irreversible cardiomyopathy [1]. The incidence of DOX-induced cardiac injury ranges from 11% to 18%, as estimated by previous studies [2,3]. The onset of DOX-induced cardiotoxicity can be acute, occurring within 2-3 days or be chronic until several months after the end of chemotherapy [3].…”
Section: Introductionmentioning
confidence: 99%